ВПЛИВ ПОЧАТКОВОЇ НАПРУГИ ЄМНІСНОГО НАКОПИЧУВАЧА ЕНЕРГІЇ ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК НА ЕЛЕКТРИЧНІ ХАРАКТЕРИСТИКИ ЙОГО КОЛИВАЛЬНОГО ЗАРЯДУ - Супруновська, Н.І.; Вінниченко, Д.В.; Михайленко, В.В. (Інститут електродинаміки НАН України, Київ, 2024)
An analysis of the transient processes of the oscillatory charge of the capacitive energy storage (CES) in the electric discharge installation (EDI) from the direct voltage source (DVS) of the UDVS was carried out under the condition of a non-zero voltage of the CES at the start time of the charge. The dependences of the maximum charging voltage of CES and energy characteristics (dosage of energy consumed from the DVS and one entered to capacitor, energy losses and efficiency) on the magnitude and sign (polarity) of the initial voltage CES and the Q factor of the charge circuit were obtained. It is shown that an increase in the absolute value of the negative initial voltage of the CES together with an increase in the Q factor of the charging circuit leads to an increase in the maximum voltage of the CES charge. The most energetically appropriate capacitor charge modes were determined. It is substantiated that increasing the initial voltage on the capacitor, as well as the Q factor of the charging circuit, leads to an increase in the charge efficiency. Analysis of the ratio between the dose of energy entering the capacitor during one charge cycle W*C and the energy losses W*losses showed that the ratio W*C / W*losses becomes larger with the change of the U0C voltage from –UDVS to + UDVS. References 15, figures 3.